Pengaruh Perceived Organizational Support (POS) dan Work Stress terhadap munculnya Perilaku Kontraproduktif dalam Perspektif Ekonomi Islam (Studi pada Karyawan PT. Gula Putih Mataram di Lampung Tengah) - Salsabiila Nur Aziizah; Ahmad Zuliansyah; Weny Rosilawati (Universitas Bumigora, 2023)
The current business competition makes companies have to carry out a mature strategic plan. Mataram White Sugar Company is a company engaged in trade manufacturing. As for the background of this research, based on pre-research that has been done, it turns out that a number of employees experience work stress, this can be caused by the absence of bonuses given, or jobs that do not match their expertise. so that it shows the existence of deviant behavior carried out by employees in the company with various types such as: going home early and damaging the existing facilities at the company, leaving late, and working unprofessionally. The research method used in this study is a quantitative method. The population used in this research is all employees of PT. Mataram White Sugar, Central Lampung. The sample used in this research is the permanent employees of PT. Mataram White Sugar. The types of data used in this research are primary data and secondary data. Where the primary data obtained through distributing questionnaires. The questionnaire was distributed to employees via gform to 92 respondents using random sampling technique. The research results of perceived organizational support have no effect on counterproductive behavior and work stress has an effect on counterproductive behavior. In an Islamic economic perspective, it emphasizes that we as Muslims must always appreciate the contributions made by others. In addition, in Islam it has provided trials that the people themselves cannot possibly overcome, so that Islam prohibits people from despairing in carrying out activities and in Islam it is also forbidden to carry out behavior that can inhibit or harm other people.